Human occupation of northern Australia by 65,000 years ago - Clarkson, Chris; Jacobs, Zenobia; Marwick, Ben; Fullagar, Richard; Wallis, Lynley; Smith, Mike; Roberts, Richard G.; Hayes, Elspeth; Lowe, Kelsey; Carah, Xavier; Florin, S. Anna; McNeil, Jessica; et al. (Nature (London), 2017)
The time of arrival of people in Australia is an unresolved question. It is relevant to debates about when modern humans first dispersed out of Africa and when their descendants incorporated genetic material from Neanderthals, Denisovans and possibly other hominins. Humans have also been implicated in the extinction of Australia’s megafauna. Here we report the results of new excavations conducted at Madjedbebe, a rock shelter in northern Australia. Artefacts in primary depositional context are concentrated in three dense bands, with the stratigraphic integrity of the deposit demonstrated by artefact refits and by optical dating and other analyses of the sediments. Human occupation began around 65,000 years ago, with a distinctive stone tool assemblage including grinding stones, ground ochres, reflective additives and ground-edge hatchet heads. This evidence sets a new minimum age for the arrival of humans in Australia, the dispersal of modern humans out of Africa, and the subsequent interactions of modern humans with Neanderthals and Denisovans. Optical dating of sediments containing stone artefacts newly excavated at Madjedbebe, Australia, indicate that human occupation began around 65,000 years ago, thereby setting a new minimum age for the arrival of people in Australia. First Australian foray pushed further into the past When did humans first colonize Australia? The date of the initial landing on the continent that is now associated with cold lager and 'Waltzing Matilda' has been highly controversial. Dates from a site called Madjedbebe in northern Australia had put the presence of modern humans in Australia at between 60,000 and 50,000 years ago, but these results have since been hotly contested. Here, the results from a comprehensive program of dating of new excavations at the site confirm that people first arrived there around 65,000 years ago. The results show that humans reached Australia well before the extinction of the Australian megafauna and the disappearance of Homo floresiensis in neighbouring Indonesia.